Magnolia lacandonica (subsection Talauma, Magnoliaceae), a new rainforest species from Chiapas, Mexico - Vázquez-García, J. Antonio; Pérez-Farrera, Miguel Ángel; Martínez-Camilo, Ruben; Muñiz-Castro, Miguel Ángel; Martínez-Meléndez, Nayely (Phytotaxa, 2013)
A new species of Magnolia from the rainforest of Chiapas, Mexico, is described and illustrated. Magnolia lacandonica belongs to section Talauma subsection Talauma and is similar to M. mexicana, but it differs from the latter in having larger number of carpels and stamens, the dorsal wall of carpels unhumped vs humped, an outer spathaceous bract topped with a reduced leaf blade vs lacking leaf blade and petals entirely white vs tinged with purple.